Borosilicate glass with low dielectric loss and low permittivity for 5G/6G electronic packaging applications - Rocio Rodriguez-Cano; Nicholas L. Clark; John C. Mauro; Michael T. Lanagan (AIP Advances)
A phase-separated borosilicate glass, with a relative permittivity ranging from 3 to 3.5 and a loss tangent as low as 5.6 × 10−4, is presented for packaging applications for the next generation of mobile communications. Ionic polarizability for each borosilicate composition was calculated from the Clausius–Mossotti relationship for both the vitreous and crystalline structures, and the polarizability difference between the two is proportional to the dielectric loss. Small amounts of alkali modifier were added to improve the glass processability, and the loss tangent increased to the 1–7 × 10−3 range. The resulting glass is phase-separated, which has no impact in the millimeter-wave spectrum, as the wavelengths are considerably greater than the length scale of each immiscible phase.